Issues in hiring and firing : papers presented at a seminar held in Brisbane on 10 April 2003 - Coulthard, Amanda (Legalwise Seminars, 2003)
An understanding of executive placements and post departure issues are discussed. Termination for misconduct is examined including how to handle misconduct and conduct outside of business hours. How to protect your business, negotiate confidentiality, intellectual property and post employment restraints are also examined.